Black glass [large type] : short fictions - Fowler, Karen Joy (Center Point Large Print, 2015)
"In fifteen gemlike tales, Fowler lets her wit and vision roam freely, turning accepted norms inside out and fairy tales upside down--pushing us to reconsider our unquestioned verities and proving once again that she is among our most subversive writers"--